Modified Tuned Liquid Dampers for Seismic Protection of Buildings Considering Soil–Structure Interaction Effects - Kamgar, Reza; Gholami, Fatemeh; Zarif Sanayei, Hamed Reza; Heidarzadeh, Heisam (Iranian journal of science and technology. Transactions of civil engineering, 2020)
Considering the effect of soil–structure interaction in dynamic analysis of structures can change their responses. It is generally assumed that the structure is located on a rigid foundation and the flexibility effect of the soil is not considered. Researches on the soil–structure interaction show that the dynamic response of the structures located on a soft and flexible soil is completely different from the dynamic response of the same structure located on a stiff soil. In this paper, the effect of the soil–structure interaction on the response of a single-degree-of-freedom system (Nagasaki airport tower) that is controlled by a modified tuned liquid damper is investigated. The soil effect is modeled using an approximate cone method based on the semi-infinite boundary conditions. First, the governing equations for describing the fluid sloshing obtained with shallow water wave theory are solved by Lax’s finite-difference scheme. Then, the dynamic equilibrium equations for a structure controlled with a modified tuned liquid damper are obtained by considering the effect of soil–structure interaction using Lagrange’s method. These equations are solved numerically by Newmark’s method. The controlled structural responses are calculated in different time steps and compared with the responses of the uncontrolled structure. Results show that the seismic design of the modified tuned liquid damper system can be more effective to reduce the structural responses. Also, this system can reduce efficiently the maximum responses of the structures considering soil–structure interaction effect during a near-fault earthquake.